Socio-ecological factors influencing boro rice yield and profitability in Wetland areas of Bangladesh: an integrated assessment - Jasim Uddin Ahmed; Md. Abul Kashem; Md. Jaynal Abedien; Tukir Ahamed; Arifa Jannat; Md. Monirul Islam (Discover Agriculture)
Abstract Many studies have examined various aspects of rice cultivation in Bangladesh, such as yield, sustainability, and the socioeconomic conditions of farmers. However, there is a noticeable gap in field-based research explicitly addressing the productivity, profitability, and challenges Boro rice producers face in wetland areas of Bangladesh. To address this gap, the current study assessed the productivity and profitability of different rice farming systems in the wetland areas of Sunamganj district, Bangladesh. Utilizing farm-level survey data, the study assessed opportunities and constraints to increase the productivity and profitability of Boro rice across diverse farming systems. The data were collected from 60 out of 157 farmers who cultivated Boro rice using a purposive sampling technique. A cost and return analysis was conducted to calculate the profitability of Boro rice cultivation in wetland areas of Bangladesh. The Cobb–Douglas production function was used to identify the factors that influence Boro rice yield in these regions. For BRRIDhan28 and BRRIDhan29 rice production, small farmers (US$2206.57) and landless farmers (US$342.55) had the highest net returns per hectare (ha) [(Alam and Swapan (2011) classified farms into four landholding-sized classes: marginal (< 0.4 ha), small (0.41–1.01 ha), medium (1.02–3.03 ha), and large (3.03 ha)]. Under BRRIDhan28 and BRRIDhan29 rice cultivation, the mean benefit–cost ratio (BCR) was 1.26 and 1.55. In the case of BRRIDhan28, the average per hectare total cost of rice cultivation was US$552.6, and in the case of BRRI Dhan29, it was US$441.71. The Cobb–Douglas production function findings reveal that the coefficient of human labor and the amonut of seed had a significant impact on Boro rice production. The study also identified constraints to rice cultivation in the wetland areas of Bangladesh, including high labor prices, inadequate irrigation facilities, fertilizer availability, quality seed, insect infestation, early flash floods, and low rice prices during harvest. Therefore, subsidies or financial support should be provided to make quality seeds, fertilizers, and irrigation facilities more affordable. Given the significant impact of the amount of seeds and human labor on Boro rice yields, improving access to these inputs will enhance the productivity and profitability of Boro rice production in wetland areas of Bangladesh.